FINANCIAL RATIO IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) (CASE STUDY: MAKASSAR PERFUME SAFARI SHOP) - Hasan, Muhammad Ridwan; Ibrahim, Mardiana; Balele, Andi Bintang (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study aims to analyze the financial ratio of MSMEs of Makassar Perfume Safari Shop which includes liquidity ratio, solvency ratio, activity ratio, and profitability ratio. This study uses a quantitative descriptive method to analyze the financial performance of MSMEs of Makassar Perfume Safari Shop through liquidity, solvency, activity, and profitability ratios. Primary data is obtained through interviews, while secondary data comes from financial statements for a specific period. Data collection was carried out through literature studies, observations, interviews, and documentation. The results of the analysis are presented in the form of financial ratio calculations to describe financial conditions systematically. The results of this study show that Makassar Perfume Safari Shop MSMEs for the 2022-2024 period have strong liquidity and solvency and are able to meet obligations and maintain a healthy capital structure. However, in 2024 there will be a decline in the effectiveness of asset and working capital utilization, accompanied by a downward trend in profitability in most indicators, so an appropriate management strategy is needed to optimize performance and restore the ability to generate profits.Keywords: Financial ratio; liquidity; solvency; activities; profitability; MSMEs